A Comprehensive Evaluation of a Two-Channel Portable Monitor to “Rule in” Obstructive Sleep Apnea - Ward, Kim L.; McArdle, Nigel; James, Alan; Bremner, Alexandra P.; Simpson, Laila; Cooper, Matthew N.; Palmer, Lyle J.; Fedson, Annette C.; Mukherjee, Sutapa; Hillman, David R. (Journal of clinical sleep medicine, 2015)
We hypothesized that a dual-channel portable monitor (PM) device could accurately identify patients who have a high pretest probability of obstructive sleep apnea (OSA), and we evaluated factors that may contribute to variability between PM and polysomnography (PSG) results. Consecutive clinic patients (N = 104) with possible OSA completed a home PM study, a PM study simultaneous with laboratory PSG, and a second home PM study. Uniform data analysis methods were applied to both PM and PSG data. Primary outcomes of interest were the positive likelihood ratio (LR+) and sensitivity of the PM device to "rule-in" OSA, defined as an apnea-hypopnea index (AHI) ≥ 5 events/h on PSG. Effects of different test environment and study nights, and order of study and analysis methods (manual compared to automated) on PM diagnostic accuracy were assessed. The PM has adequate LR+ (4.8), sensitivity (80%), and specificity (83%) for detecting OSA in the unattended home setting when benchmarked against laboratory PSG, with better LR+ (> 5) and specificity (100%) and unchanged sensitivity (80%) in the simultaneous laboratory comparison. There were no significant night-night (all p > 0.10) or study order effects (home or laboratory first, p = 0.08) on AHI measures. Manual PM data review improved case finding accuracy, although this was not statistically significant (all p > 0.07). Misclassification was more frequent where OSA was mild. Overall performance of the PM device is consistent with current recommended criteria for an "acceptable" device to confidently "rule-in" OSA (AHI ≥ 5 events/h) in a high pretest probability clinic population. Our data support the utility of simple two-channel diagnostic devices to confirm the diagnosis of OSA in the home environment. A commentary on this article appears in this issue on page 411.